Catalytic hydrothermal processing of lipids using metal doped zeolites. (March 2017) - Robin, Thomas; Jones, Jenny M.; Ross, Andrew B.
Abstract: A range of vegetable oils with different lipid compositions have been processed under hydrothermal conditions in the presence of transition metal doped zeolites (containing molybdenum, chromium, cobalt and iron). The lipids processed include sunflower, soybean, jatropha, palm and linseed oils over a temperature and pressure range of 250–350 °C and 12–17 MPa respectively. The products have been analyzed using a combination of GC-MS, FAME analysis, size exclusion chromatography (SEC), and simulated distillation (using thermogravimetric analysis TGA). Hydrothermal processing of lipids results in the hydrolysis of the triglycerides at low temperatures. Lipids high in polyunsaturated fatty acids such as linoleic and linolenic acid promote cross linking and cyclization reactions resulting in "heavier molecular weight" wax-like material. Saturated fatty acids such as palmitic and stearic acids are more stable. Some of the catalysts, such as un-doped zeolite (HZSM-5) and molybdenum doped zeolite (MoZSM-5) favor the formation of alkenes and aromatic compounds in the kerosene and gasoline boiling point range. Highlights: Catalytic hydrothermal processing of lipids can produce kerosene and gasoline range hydrocarbons. The presence of polyunsaturated fatty acids can increase likelihood of cross-linking reactions. MoZSM-5 and HZSM-5 increase level of aromatic and aliphatic hydrocarbons in the bio-crude. Catalytic hydrothermal processing of Sunflower oil produces a high kerosene fraction.